Generative systems in the architecture, engineering and construction industry: A systematic review and analysis. (September 2021) - BuHamdan, Samer; Alwisy, Aladdin; Bouferguene, Ahmed
Researchers have been extensively exploring the employment of generative systems to support design practices in the architecture, engineering and construction industry since the 1970s. More than half a century passed since the first architecture, engineering and construction industry's generative systems were developed; researchers have achieved remarkable leaps backed by advances in computing power and algorithms' capacity. In this article, we present a systematic analysis of the literature published between 2009 and 2019 on the utilization of generative systems in the design practices of the architecture, engineering and construction industry. The present research studies present trends, collaborations and applications of generative systems in the architecture, engineering and construction industry in order to identify existing shortcomings and potential advancements that balance the need for theory development and practical application. It provides insightful observations that are translated into meaningful recommendations for future research necessary to progress the incorporation of generative systems into the design practices of the architecture, engineering and construction industry.